2017
DOI: 10.1111/radm.12274
|View full text |Cite
|
Sign up to set email alerts
|

R&D capabilities, intellectual property strength and choice of equity ownership in cross‐border acquisitions: evidence from BRICS acquirers in Europe

Abstract: The aim of the study is to investigate two relatively underexplored factors, namely, the R&D (research and development) capabilities of target firms and the strength of intellectual property (IP) institutions in target economies, that influences the choice of equity ownership in cross border acquisitions (CBAs) undertaken by multinational enterprises (MNEs) from BRICS (Brazil, Russia, India, China and South Africa) economies. They developed the key hypothesis on foreign market entry through CBAs by incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 97 publications
0
30
0
Order By: Relevance
“…The same results are also reflected in R&D‐intensive industries, where the possibility of reverse innovation from target firms leads to full rather than partial acquisitions (Ahammad et al. 2018). In contrast, some scholars have found that acquirers prefer to share the equity with the target firm in high‐technology industries, which helps to reduce the risk from information asymmetry (Chari & Chang 2009) and to co‐develop capabilities through equity collaboration (Zhao & Zhu 1998).…”
Section: Determinants Of Equity Ownership Decisions: Theoretical Frammentioning
confidence: 76%
See 1 more Smart Citation
“…The same results are also reflected in R&D‐intensive industries, where the possibility of reverse innovation from target firms leads to full rather than partial acquisitions (Ahammad et al. 2018). In contrast, some scholars have found that acquirers prefer to share the equity with the target firm in high‐technology industries, which helps to reduce the risk from information asymmetry (Chari & Chang 2009) and to co‐develop capabilities through equity collaboration (Zhao & Zhu 1998).…”
Section: Determinants Of Equity Ownership Decisions: Theoretical Frammentioning
confidence: 76%
“…For instance, host institutional environments, such as institutional advancement and strength of intellectual property protection in the host country, reduce the need for the acquirer to opt for full rather than shared ownership structure (Ahammad et al. 2018; Dikova & Van Witteloostuijn 2007), while regulatory distance increases the need for a higher degree of control over the target firm with high R&D intensity (Zhang et al. 2014).…”
Section: Determinants Of Equity Ownership Decisions: Theoretical Frammentioning
confidence: 99%
“…First, we study the previously unidentified determinants of the strength of enforcement of patent law in practice for 43 WTO member countries in the post-TRIPS years, 1998-2011. We follow the same methodology as Ginarte and Park; however, we use the composite index of patent systems strength developed by Papageorgiadis et al (2014) to approximate for the strength of the enforcement of patent law in practice (Ahammad et al, 2018;. 3 We find strong and consistent evidence that higher numbers of patent and trademark applications filed in a country have a significantly positive effect on the strengthening of the enforcement of patent law in practice.…”
Section: Introductionmentioning
confidence: 92%
“…Foley et al (2006) study the effect of IPRs reforms on US multinationals, finding that stronger IPRs increase technology transfer and the level and growth rate of non-resident patenting. Ahammad et al (2018) find that the greater the strength of IP protection in target economies and higher the target firms' research and development (R&D) capabilities, the more likely it is for multinational companies of Brazil, Russia, India, and China to undertake partial, rather than full acquisitions. On the contrary, other authors find a negative or not significant correlation between IPRs and FDI.…”
Section: Determinants Of Mandas and The Effect Of Iprsmentioning
confidence: 99%